Observation of environments with different restorative potential results in differences in eye patron movements and pupillary size - Martínez Soto, Joel; De la Fuente Suárez, Luis Alfonso; Gonzáles Santos, Leopoldo; Barrios, Fernando A. (Elsevier, 2019)
The Environmental Psychological Restoration (EPR) is the result of the recovery of an antecedent deficit (e.g. stress or attentional fatigue) culminating in a restorative environment exposure. Recent findings suggest that visual contact with nature is important in triggering restorative responses. We measure the behavioral evidence of visual exposure to restorative environments in an eye-tracking study. Eye movement patterns (fixations and pupil dilatation) were evaluated while a sample of participants (n = 27; 15 females and 12 males) viewed photographs with High Restorative Potential (HRP) or Low Restorative Potential (LRP). The eye patterns during the observation of LRP were distinct to those of the HRP environments. Eye movements related to LRP photographs were characterized by a greater number of fixations compared to those related to HRP. Fixation times predicted an inverse relation, with LRP settings having a significantly shorter time per fixation than HRP pictures. Differences on pupil diameter were found. A higher pupil size was found during the view of HRP vs. LRP environments. Our eye tracking study suggest that restorative environment observation is associated with reduced eye movement activity relative to low restorative potential environment perception, which may reflect a lower cognitive effort in processing natural scenes. Likewise, pupillary dilatation variations suggest a possible link between the affective valences of the settings and its restorative quality. Data results are confronted according to attention restoration theory on restorative environments. Keywords: Restoration, Fatigue, Restorative potential, Eye tracking, Pupil dilation, Fixation